Gender and employee involvement in Malaysia - Norsiah Aminudin, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This paper examines the differences between the attitudes of men and women towards Employee Involvement (EI) programs in Malaysian context. Quality Circes (QC)and Employee Share Ownership Schemes (ESOS) were the focus of the current study of EI. Both quantitative research approaches were used in amixed method study. The research found no significant differences in the attitudes of men and women toward EI schemes. However, with regard to participating in EI programs men appeared to have more opportunity in comparison to women.This suggests that managers should seriously consider gender variations in designing EI schemes at the workplace.